Description of the first zoea of fiddler crab Uca ornata, (Smith, 1870) (Decapoda, Ocypodidae) - Ramos Veliz, John Alex (2024)
Fiddler crabs are the most representative brachyurans in estuaries; they are within the Ocypodidae family where males present strong sexual dimorphism due to a process called hetero-chelation, they also have a great adaptive capacity from their larval stage, so studies that cover part of the development of these organisms are necessary, Uca ornata (Smith, 1870) is a crab that has few ecological and taxonomic studies and the larval description is a fi rst step, for this, U. ornata larvae obtained in captivity were analyzed, where diagrams of the fi rst larval stage were made, including a description of the relevant taxonomic characteristics with the aid of optical microscopy and microscope camera. Th e results were compared with other species of fi ddler crabs of the same genus, fi nding that these characteristics allow these species to be diff erentiated even if they are from diff erent geographical áreas.